How Do Perceived Social Support and Community Social Network Alleviate Psychological Distress During COVID-19 Lockdown? The Mediating Role of Residents' Epidemic Prevention Capability - Zhao, Xu; Jin, Aolan; Hu, Bin (Frontiers in Public Health, 2022)
Aim: Following the outbreak of the COVID-19 epidemic, China adopted community isolation management measures. During the “lockdown” period, urban communities were the most basic prevention and control unit for the epidemic. The effectiveness of community epidemic prevention directly affects the spread of the virus and social stability. Therefore, the aim of this study was to explore the status quo and influencing factors of psychological distress. Methods: For this study, 1,430 community households were randomly selected in key cities affected by the epidemic, and a questionnaire survey was administered during the lockdown period. A structural equation model was used to analyse the influencing factors of community epidemic prevention effects. A total of 1,326 valid questionnaires were collected, with a valid response rate of 92.73%. Results: In this study, the differences in psychological distress among different community types were statistically significant (t=58.41, P<0.01). The results showed that epidemic prevention capability played a mediating role. The results of the high-order structural equation model analysis showed that perceived social support (β=-0.275, P=0.000)and community social network (β=-0.296, P<0.05) were significantly negatively correlated with psychological distress. Conclusions: Community social support not only has a direct impact on the effect of epidemic prevention but also has an indirect effect on prevention and control by improving residents’ defence ability. The community social network help residents reduce the risk of epidemics and indirectly alleviate psychological distress.